Smokeless Tobacco Use and Quit Behaviour Assessment in a Middle Aged to Elderly Population in a Rural Setting - An Evaluative Study - Hunny Sharma; G.Y. Yunus; Swati Verma; Rohit Agarwal; Ramakrishna Chevvuri; Balasubramanyam Vasant (Wolters Kluwer Medknow Publications, 2024)
Introduction: Expanding knowledge on tobacco use and quitting outcomes in Chhattisgarh, India, is crucial. Limited data hinder the assessment of tobacco use prevalence and quitting outcomes in the region. This household-based cross-sectional study aimed to assess smokeless tobacco (SLT) use and quit behaviour among village dwellers aged 35-44 and 65-74 years in Jamul, Chhattisgarh. Materials and Methods: A survey was conducted among 450 participants, utilising a pretested questionnaire and data analysis using IBM Statistical Package for the Social Sciences (SPSS) v23. Results: The study revealed that among the survey participants, 61.1% were males and 38.9% were females. The prevalence of SLT use was found to be 67.8%, with 59.1% of current SLT users reporting daily use. Middle-aged individuals predominantly chose gutkha, while khaini was more common among the elderly. Tobacco and paan with tobacco were also commonly used forms. Gudakhu, a popular SLT product for oral hygiene and easy defecation, was reported by 71.34% of participants. Television warnings and SLT packages proved to be successful methods for disseminating information about the dangers of SLT use. However, SLT users who attempted to quit independently reported encountering one or more withdrawal symptoms, which posed significant obstacles to quitting SLT. Conclusion: Community-based awareness programmes are implemented via regional television (TV) channels, coupled with cessation initiatives, including professional counselling, pharmaceutical interventions and support of peer. Changing attitudes against SLT use and promoting tobacco-free environments are prioritized. These strategies will effectively address SLT use and improve quitting outcomes in Jamul, Chhattisgarh, fostering a healthier community.